2010
DOI: 10.1002/jmv.21773
|View full text |Cite
|
Sign up to set email alerts
|

Neurovirulence and latency of drug‐resistant clinical herpes simplex viruses in animal models

Abstract: Herpes simplex virus (HSV) resistance to acyclovir or foscarnet results from mutations in viral thymidine kinase (TK) and/or DNA polymerase (pol) genes. Replication kinetics and virulence of TK and/or DNA pol clinical mutants were assessed using models of mouse encephalitis and cotton rat genital infection. Replication capacities in Vero cells of a DNA pol altered strain (L850I) and a TK/DNA pol mutant (C467deletion/A912V) were significantly lower than those of unrelated wild-type (WT) strains, while a double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Interestingly, no isolate was assigned as genotype A that represents nearly 50% of all strains included in this study. Using animal models, previous reports have shown that clinical HSV‐1 isolates differ in virulence [Reefschläger et al, 1986; Bower et al, 1999; Dambrosi et al, 2010]. However, Norberg et al [2004] were unable to demonstrate an association between specific sequences of gG as well as gI genes and anatomical sites of lesions, including brain.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no isolate was assigned as genotype A that represents nearly 50% of all strains included in this study. Using animal models, previous reports have shown that clinical HSV‐1 isolates differ in virulence [Reefschläger et al, 1986; Bower et al, 1999; Dambrosi et al, 2010]. However, Norberg et al [2004] were unable to demonstrate an association between specific sequences of gG as well as gI genes and anatomical sites of lesions, including brain.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinvasiveness is expected to correlate with viral fitness, so that highly replicating viruses would be more neurovirulent. Recently, it has been shown that the degree of neurovirulence of several DNA pol mutants could be generally predicted by their in vitro replicative capacity (67). However, Pelosi et al (163) reported a DNA pol mutant (R842S) that could replicate in the central nervous system but, paradoxically, exhibited attenuated neurovirulence.…”
Section: Pathogenesis Of Drug-resistant Hsv Strains In Animal Models/mentioning
confidence: 99%
“…While acyclovir and related nucleoside analogues provide successful modalities for treatment and suppression, HSV remains highly prevalent worldwide. The emergence of acyclovir-resistant virus strains, ability of virus to uniformly establish latency coupled with adverse effects of available anti-herpetic compounds provides a stimulus for increased search for new effective antiviral agents that target additional steps in viral pathogenesis such as entry (Schutle et al, 2010; Dambrosi et al, 2010). In addition, the current available treatments are unable to destroy HSV completely and therefore virus remains dormant and keeps activating from time to time to cause various clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%